2019
DOI: 10.21037/jtd.2019.03.57
|View full text |Cite
|
Sign up to set email alerts
|

Novel approach for predicting occult lymph node metastasis in peripheral clinical stage I lung adenocarcinoma

Abstract: Background: Occult nodal metastasis results in a poor prognosis for lung cancer patients. The aim of this study was to develop an efficient approach for predicting occult nodal metastasis in peripheral clinical stage I lung adenocarcinoma. Methods: Data for 237 peripheral clinical stage I lung adenocarcinoma patients who underwent complete resection were retrospectively reviewed. Univariate and multivariate analyses were performed to investigate predictors of occult nodal metastasis. Kaplan-Meier analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…Other factors should be considered. Similar to previous studies (19,22), a higher serum CEA (OR: 1.247, 95%CI: 1.110-1.402, P < 0.001) was also associated with a higher LNM rate in our study. Thus, the serum CEA level might be helpful for LNM prediction and should be listed as a routine test for NSCLC patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other factors should be considered. Similar to previous studies (19,22), a higher serum CEA (OR: 1.247, 95%CI: 1.110-1.402, P < 0.001) was also associated with a higher LNM rate in our study. Thus, the serum CEA level might be helpful for LNM prediction and should be listed as a routine test for NSCLC patients.…”
Section: Discussionsupporting
confidence: 91%
“…Previously, our (20) and other studies (19,(21)(22)(23) have found that several preoperative factors might be associated with the occurrence of LNM in small-size NSCLC, including serum CEA, tumor size and imaging features such as imaging density. Tumor size was identified as an important predictor for LNM.…”
Section: Discussionmentioning
confidence: 65%
“…Using conventional univariate analysis, previous studies reported the risk factors associated with LNM in NSCLC ≤ 2 cm, including tumor size, serum CEA and imaging density (30,31). In addition, SUV max was also thought to be a risk factor in patients with cT1 NSCLC (32). Thus, the AUCs when using tumor size (AUC = 0.753), SUV max (AUC = 0.734), or CEA (AUC = 0.720) alone were also calculated, which were significantly lower than those of MLbased models ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, another one of the valuable prognostic factors in primary pulmonary PA was lymph node involvement [14]. Ikuo et al revealed the higher occult nodal metastasis rate in PPA subtype (17/154, 11.0%) and SPA subtype (2/7, 28.6%) (both P=0.001) in comparison with additional subtypes through retrospectively analyzing 237 patients with peripheral clinical stage I lung adenocarcinoma [15]. In our current study, 38.4% of pulmonary PA exhibited positive lymph node invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In the light of current literature review, our study developed the first nomogram to predict the survival and prognosis of patients with pulmonary PA based on SEER database. Nevertheless, our nomogram did not include other clinical information, including pivotal clinical symptoms, imaging presentations, and comprehensive laboratory indicators such as serum tumor markers [15]. More importantly, accumulating clinical studies revealed the identification of such tumors with alterations in genes such as ALK [21], epidermal growth factor receptor (EGFR) [22][23][24][25], which was momentous to guide tyrosine kinase inhibitors (TKIs) therapy.…”
Section: Discussionmentioning
confidence: 99%